Assessing insulin sensitivity and resistance in syndromes of severe short stature. (August 2020) - Guevara-Aguirre, Jaime; Teran, Enrique; Lescano, Daniela; Guevara, Carolina; Guevara, Alexandra; Saavedra, Jannette; Procel, Patricio; Wasserfall, Clive; Gavilanes, Antonio W.D.
Abstract: Individuals affected with two genetic syndromes identified in Ecuador have severe short stature and diminished insulin secretion, along with essentially different GH counterregulatory effects on insulin action, which leads to the appearance of opposing metabolic phenotypes. In the case of Laron syndrome, subjects have enhanced insulin sensitivity and diminished incidence of type 2 diabetes mellitus. In the other clinical entity, individuals have innate insulin resistance, a varying degree of carbohydrate metabolism disturbances, glucose intolerance, and eventually insulin-resistant diabetes mellitus. Since both groups have diminished insulin secretion, the standard homeostatic minimal models for assessment of insulin sensitivity and resistance were used to see if they could properly identify the metabolic status, especially considering that these methodologies are simple and non-invasive procedures. Methods: Fasting insulin concentrations, fasting glucose/fasting insulin ratio and various minimal models were determined in individuals from the two syndromic cohorts, as well as in a control group made of first-degree normal relatives of the insulin-resistant phenotype subjects. Results: The metabolic characteristics of enhanced insulin sensitivity in one of the syndromes and innate insulin resistance in the other could not be properly ascertained by the selected methodology. Furthermore, results were confusing and even discrepant with the clinical findings. Conclusions: The standard homeostatic minimal models could not properly identify or discriminate insulin sensitivity and resistance in subjects with inherently diminished secretion. It is thereby suggested that these models should be used with caution in clinical situations where reduced secretion of the metabolic peptide is found or suspected. Highlights: The homeostatic minimal models are low cost and non-invasive methods for assessment of insulin sensitivity in clinical conditions. Fasting insulin; G/I ratio; and HOMA, QUICKI, Belfiore, Avignon, Gutt, Matsuda, Stumvoll, and McAuley indexes were determined. The phenotypes defined by enhanced insulin sensitivity or by innate insulin resistance could not be tested by the homeostatic models. Homeostatic models did not match to the clinical phenotype in subjects with diminished insulin secretion and reduced pancreatic reserve.